Cases of Monkeypox show highly-overlapping co-infection with HIV and syphilis - Jia, Lin; Yan, Benyong; Fang, Yuan; Yang, Xiaodong; Jia, Han; Zhang, Mei; Li, Shuang; Zhang, Yang; Wang, Wen; Guo, Caiping; Zhang, Tong; Huang, Xiaojie; et al. (Frontiers in Public Health, 2024)
Purpose Ongoing Monkeypox (MPX) outbreaks in countries outside Africa have unique characteristics. However, data on cohorts of confirmed cases in China is limited. The study provides important epidemiological, diagnostic, and clinical information about this disease in China. Methods We report a series of Chinese individuals with confirmed MPX infections identified at Beijing Youan Hospital (China) from June 10 to July 15, 2023. Samples were taken from the skin, anus, throat, and blood. An epidemiological questionnaire was used to collect demographic and clinical data. Further, we compared the MPX viral (MPXV) loads across different anatomical sites. Results 66 samples were collected from 20 patients, all of whom were cisgender men. Median patient age was 29 years. Notably, 19 (95%) patients reported unprotected sexual encounters with men in the preceding month, and 13 (65%) were human immunodeficiency virus (HIV)-positive. Among those with HIV, 12 (92%) were receiving antiretroviral therapy, and 11 (85%) had well-controlled infections (HIV viral load <40/mL). The median CD4+ T cell count was 667 cells/mm3. In the HIV-negative group, three (43%) patients were taking preexposure prophylaxis. Fifteen patients (75%) had concurrent sexually transmitted infections (50% had syphilis and 65% had HIV) and eight (40%) had HIV and syphilis co-infection. MPXV loads were significantly higher in samples from the skin (cycle threshold value [Ct value]: 19·0) and anus (Ct value: 23.0) compared to samples from the throat (Ct value: 31.0) or blood (Ct value: 34.5). All patients had skin lesions (85% of whom presented with anogenital lesions). Common systemic symptoms included fever (85%) and lymphadenopathy (55%). The median incubation period was 8 d [interquartile range (IQR): 6–16 d]. The median time from the onset of skin lesions to scab removal was 14 d (IQR: 10–16 d). No deaths or severe cases were reported. Conclusion MPXV primarily affects young homosexual men. The high MPXV viral loads in skin and anal lesions indicate that transmission most likely occurs through direct and close body contact. This study also reports high rates of HIV and syphilis co-infection. Therefore, preventive efforts should focus on homosexual men.